Modeling of drug release from nanophase hydroxyapatite carriers – statistics in action - Kalambettu, Narasimha Raghavan R.* and Aravind Bhat (Journal of Experimental Sciences, 2011)
Mathematical modeling of drug release from a biomaterial, with respect to time and other factors assumes paramount importance in the field of drug delivery. In this study, doxycycline containing hydroxyapatite ceramics, placed in physiological saline for 10 days, was taken as a model. Numerical equations were derived and curve fitting was done with the observed values. The relations between various parameters and release curve were studied. The observations were verified numerically. The results of the study showed that the drug release can be quantified predictably and controlling the release is possible. Future scope of the study is also discussed.